Modification of Strength Properties of Oxide Materials by Ion Irradiation; Key Engineering Materials; Vol. 781 : Radiation-Thermal Effects and Processes in Inorganic Materials - Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Kostenko V. Valeriya; Shevelev S. A. Sergey Anatolievich; Kupchishin A. I. Anatoliy Ivanovich; Kondratyuk А. А. Alexey Alekseevich (2018, 2018)
Title screen